Peran Keluarga dalam Memotivasi Anak Usia Dini dengan Metode Quantum Learning - Dewi Mayangsari; Vitrotul Umroh (Universitas Trunojoyo Madura, 2014)
This study aims to determine how the role of parents when accompanying their children while studying at home and find out how the family can motivate children. In this study takes an object of early childhood to the age of about 3-6 years and parents who accompany.Methods used in this activity is the observation and interviews conducted in the village park, Sidoarjo. The results obtained are motivated child begins to increase when parents are able to give attention and learning quantum methods bring an atmosphere of fun for children as encourage learning outside.